Հայ–բիւզանդական յարաբերութիւնները Է դարի կէսերին եւ Զուարթնոցի տաճարի կառուցման ժամանակը - Յակոբեան, Ալեքսան («Զանգակ - 97»)
A comparative study of historic sources has revealed that Zuartnots Cathedral was built between the years 650 to 660, rather than between 642 to 652, as traditionally believed. Sebeos wrote about the starting of its construction, telling that it happened after the end of the 647-650 Byzantine-Arab war. As for the end of the construction, information is provided by two sources, which Movses Daskhurantsi, the author of late 10th century, included into, or used in his "History of Albania". The first one is the work by an Anonymous Historien conditionaly named "The History of the Year 684", and the second one is the collection entitled "The List of Albanian Catholicoses", which was compiled, most likely, in early 10th century, but was based on "Diary notes" of clergymen, who were witnesses of events of 7-10th centuries. Comparative analysis of information of these sources shows that Byzantine Emperor Constant II was in Armenia in early spring of 660, and attended the consccration ceremony of the Zuartnots Cathedral, built with his sponsorship near the old capital of Valarshapat.
Keywords: Հայոց պատմութիւն